Multidisciplinary Analysis of Islamic Religious Education Development in the Digital Transformation Era - Ahmad Nabriz; Ramadan Basher Imhemd; Nail Okuyucu (Al-Mukhlashin: Jurnal Multidisiplin Ilmu, 2025)
The purpose of this research is to explore the development of Islamic religious education amid digital transformation using a multidisciplinary approach. This study applies a library research method by analyzing classical and contemporary literature. The results show that integrating educational science, communication studies, and Islamic studies enhances curriculum relevance, learning innovation, and moral formation. Digital transformation provides opportunities and challenges that require adaptive educational strategies